2023
DOI: 10.3389/fpls.2022.1102341
|View full text |Cite
|
Sign up to set email alerts
|

Fusarium head blight monitoring in wheat ears using machine learning and multimodal data from asymptomatic to symptomatic periods

Abstract: The growth of the fusarium head blight (FHB) pathogen at the grain formation stage is a deadly threat to wheat production through disruption of the photosynthetic processes of wheat spikes. Real-time nondestructive and frequent proxy detection approaches are necessary to control pathogen propagation and targeted fungicide application. Therefore, this study examined the ch\lorophyll-related phenotypes or features from spectral and chlorophyll fluorescence for FHB monitoring. A methodology is developed using fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 57 publications
1
1
0
Order By: Relevance
“…The studies also used SVM and RF models, but KNN outperformed the competing models. Moreover, the studies have also concluded that the comparative performance of disease-specific or newly developed indices for model fitting is highly improved against conventional indices [45,89] that support different other studies [99]; based on these results, a precise FHB monitoring program can be developed. Moreover, the better disease estimation performance of models through disease-specific indices or bands has also been proved by previous findings [42,99].…”
Section: Quantitative Models For Scab Diseasesupporting
confidence: 52%
See 1 more Smart Citation
“…The studies also used SVM and RF models, but KNN outperformed the competing models. Moreover, the studies have also concluded that the comparative performance of disease-specific or newly developed indices for model fitting is highly improved against conventional indices [45,89] that support different other studies [99]; based on these results, a precise FHB monitoring program can be developed. Moreover, the better disease estimation performance of models through disease-specific indices or bands has also been proved by previous findings [42,99].…”
Section: Quantitative Models For Scab Diseasesupporting
confidence: 52%
“…Numerous studies have used univariate and multivariate quantitative models for disease estimation in ARS for diverse plant diseases [98]. Different studies estimated the scab disease at spike [89] and canopy scale [45] using KNN predictive model. The studies also used SVM and RF models, but KNN outperformed the competing models.…”
Section: Quantitative Models For Scab Diseasementioning
confidence: 99%
“…[96] and Zhang et al [97] captured wheat ears from the front and back to obtain spectral information on them with possible differences in infection levels on each side. Mustafa et al [98] captured the top, middle, and bottom of each wheat spike from both sides to obtain the chlorophyll content of each partition. Multi-directional sampling not only provides more comprehensive and accurate spectral information but also reduces the influence of natural factors such as atmosphere, lighting, and shadows through averaging processing, improving the uniformity of surface reflection of objects.…”
Section: Detection Based On Spectral Imagingmentioning
confidence: 99%
“…Moreover, data fusion breaks the shackles of traditional feature selection methods and provides more comprehensive considerations for decision-making under fine FHB severity grading indicators. In the heterologous data fusion, Mustafa et al [98] utilized the Machine Learning Sequential Floating Forward Selection (ML-SFFS) algorithm to classify the severity of FHB infection into nine levels based on multimodal data fused with HSI, CFI, and HTP; Mahlein et al [101] refined the classification criteria to ten levels by fusing data from three imaging techniques: IRT, CFI, and HSI. Both of them achieved an average accuracy of over 85%.…”
Section: Detection Based On Spectral Imagingmentioning
confidence: 99%
See 1 more Smart Citation